Cyprinid herpesvirus 3 (CyHV-3) transmission and outbreaks in Iran: Detection and characterization in farmed common carp. (December 2020) - Ahmadivand, Sohrab; Soltani, Mehdi; Shokrpoor, Sara; Rahmati-Holasoo, Hooman; El-Matbouli, Mansour; Taheri-Mirghaed, Ali
Abstract: This study shows the presence of Cyprinid Herpesvirus-3 (CyHV–3) in common carp ( Cyprinus carpio) from Iranian carp farms with cumulative mortality up to 80% during 2015–2016. Pathological signs of disease such as gill necrosis, sunken eyes, and increased slime secretion on the skin and fins were observed in affected fish. The extensive fusion of secondary lamellae with necrotic cells, margination of chromatin, and formation of intranuclear inclusion bodies in gill tissues were also observed by histopathological examination. Most tubular epithelial cells and some hematopoietic cells showed intranuclear inclusion bodies in the kidney. The Iranian CyHV-3 isolates showed identity with Asian strains, and displayed the I ++ II + allele of the Asian lineage, as revealed by sequence analysis of the TK gene, Marker I, and Marker II. The detected isolates were also similar to those detected from koi in the same region of Iran, suggesting the probable transmission of CyHV–3 from ornamental to farmed cyprinids. This represents the first report of CyHV–3 from Iranian farmed common carp to the best of our knowledge. Highlights: This is the first report of CyHV–3 in farmed common carp ( Cyprinus carpio) in Iran. Diagnosis of CyHV–3 was made by clinical, histopathological, and molecular characterization. The Iranian CyHV–3 isolates were classified as Asian lineage and displayed the I ++ II + allele. This study suggests the probable transmission of CyHV-3 from imported ornamental koi to farmed cyprinids in Iran.